Gust rejection properties of VTOL multirotor aircraft - Whidborne, James F.; Cooke, Alastair K. (Elsevier, 2018)
The effect of rotor aerodynamics on the stability and control of multi-rotor aircraft is explored by analysis of a conceptual planar birotor aircraft. In particular, the effect of rotor tilt on the stability and zero-location is investigated. Furthermore, it is shown that designing the vehicle with outwards rotor tilt potentially results in dramatic improvement in the gust rejection properties of the vehicle.
Keywords: UAV control; Quadrotors; Gust rejection; Stability; Non-minimum phase systems